Effect of combined physical exercise program on improving the functional capacity and the cardiac autonomic modulation of Chagas cardiomyopathy - Diogo Van Bavel; Wallace Machado Magalhães de Souza; Yan de Britto Nery; Juliana Nascimento Amorin; Roberto Coury Pedrosa; Michel Silva Reis (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aims: Patients with Chagas cardiomyopathy (ChC) could have a significant reduction in functional capacity (FC). This study aimed to report the effect of a 24-week combined physical exercise program on the FC of a patient with ChC. Methods: A woman, 44 years old, with positive serology for ChC in stage B2 has submitted the following assessments: i) Physical assessment: ii) Cardiopulmonary exercise test; iii) Test of 1-maximum Repetition, iv) Evaluation of cardiac autonomic modulation by heart rate variability (HRV). Results: The results obtained revealed a reduction in the anthropometric parameters and the SBP after training. Additionally, we observed an improvement in FC (aerobic and strength condiction) and cardiac autonomic modulation after 24 weeks of combined training. Conclusion: Our findings show that of a 24-week combined physical exercise program improved either FC or HRVof the patient with ChC.